Proyecto para la confección y comercialización de chaquetas de cuero para mujer, bajo la modalidad de closet, en el Cantón Quito, en la Provincia de Pichincha. - Heredia Chicaiza, Edith Fernanda (2013)
The feasibility study is an investigation into the framework of factors affecting the project as well as the legal aspects affecting it. Likewise, should investigate the different techniques (if any) to produce the good or service under study and the possibilities of adapting to the culture of the place where it is to locate the project. In addition to analyzing the availability of key inputs required for the project and conduct a market survey in roughly reflect the possibilities of the new product.